2020
DOI: 10.1109/access.2020.2996383
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding MTC at the Physical Layer: Potentials and Challenges

Abstract: 5G networks must provide a highly resilient, secure, and privacy-protected platform to support the emergence of new business and technologies expected from the so-called vertical-industry paradigm. However, as the definition and implementation of 5G networks are in progress, many security challenges arise. Thus, special emphasis will be given in the coming years to provide security and privacy for 5G and beyond networks. In this regard, physical layer security has been recognized as a potential solution to saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Also note that, for lower values of δ, the impact of LoS available on the RF links, especially on B, is more significant, as expected given that, in those conditions, the RF link is the main source of leakage to E. Moreover, it can be observed that, it is better to allocate more rate for the VLC link in terms of secrecy. On the other hand, with both B and E located at the edge of the VLC coverage, better performance is obtained as more data rate is allocated to the RF link, since according to (6), the secrecy capacity of the VLC link is based on the position of the nodes and it is only positive if B is closer to the source than E. In this case, the performance is slightly improved when E has a smaller LoS component. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also note that, for lower values of δ, the impact of LoS available on the RF links, especially on B, is more significant, as expected given that, in those conditions, the RF link is the main source of leakage to E. Moreover, it can be observed that, it is better to allocate more rate for the VLC link in terms of secrecy. On the other hand, with both B and E located at the edge of the VLC coverage, better performance is obtained as more data rate is allocated to the RF link, since according to (6), the secrecy capacity of the VLC link is based on the position of the nodes and it is only positive if B is closer to the source than E. In this case, the performance is slightly improved when E has a smaller LoS component. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Moreover, with the introduction of disruptive technologies and novel services, 6G networks must assure a high level of security and privacy, so that traditional cryptography-based techniques might not be suitable or enough for some applications, especially those of constrained scenarios, e.g. limited hardware and restricted computing power [6] . Hence, physical layer security (PLS) techniques might found a new horizon on 6G to provide security by efficiently exploiting the randomness of wireless channels.In this regard, there exists special interest in investigating PLS techniques on VLC networks under secrecy constraints [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem, physical layer authentication (PLA) emerge as a viable solution to provide secure communications with low latency and light signalling overhead, compatible with IoV applications, by relying on the unique channel properties or inherent attributes of communication devices to perform the authentication of vehicles [86], [87]. Based on this, [88] proposed a V2X PLA scheme that uses a Kalman filter to refine the iterative model and threshold model in the authentication mode.…”
Section: G Physical Layer Authentication and Key Generationmentioning
confidence: 99%
“…Disruptive technologies, such as SDN and NFV, allow the deployment of customized security configurations, thus enabling the deployment of security-as-a-service [77]. By exploiting the physical properties and randomness of wireless channels, physicallayer security techniques are considered promising solutions to complement upper layer schemes and provide compatible solutions with the requirements of MTC networks [78]. Thus, those techniques may find a place in the definition of 6G security solutions.…”
Section: Potential Security Privacy and Trust Enablersmentioning
confidence: 99%